Silicon Oxynitride Optical Waveguide Ring Resonator Utilizing a Two-Mode Interferometer Structure - Kaixin Chen; Hau Ping Chan (International Journal of Photoenergy)
Silicon oxynitride (SiOxNy, SiON) optical waveguide ring resonator, in which a two-mode interferometer is used to replace the directional coupler in a conventional ring resonator, has been designed and fabricated. Preliminary results exhibit the same of free spectral range of 100 GHz but different quality factors of 3700 and 3900 at 1550 nm for transverse electric (TE) and transverse magnetic (TM) mode, respectively. The extinction ratio is more than 18 dB over the entire C-band, and the insertion loss is lower than 9.5 dB for TE and TM mode.